Hipoglikemia Persisten pada Neonatus Prematur, Kecil Masa Kehamilan (KMK), dan Berat Badan Lahir Rendah (BBLR) dari Ibu dengan Riwayat Preeklampsia Berat: Laporan Kasus - Putri, Asterisa Retno; Arumndari, Runi; Liman , Claudia Natasha; Suryaningsih , Putu Siska (PT Kalbe Farma Tbk., 2024)
Background: Neonatal hypoglycemia is a metabolic problem that is often found in the NICU and is one of the causes of permanent brain damage in infants. The diagnosis of persistent hypoglycemia and its causes are still controversial. Case: A male baby was born to a mother with severe preeclampsia at 36 weeks of gestation, with a birth weight of 1600 grams. At 1 hour of age, he experienced hypoglycemia that lasted more than 72 hours with the lowest blood sugar of 18 mg/dL, and experienced hyperkalemia (potassium level 6.1 mmol/L). The baby is diagnosed as persistent hypoglycemia. The clinical condition improved after being given dextrose and dexamethasone, and was discharged in stable condition. Conclusion: Management of persistent hypoglycemia depends on the cause. Diagnosis refers to risk factors before or after birth.